PENGARUH EKSPOR, KURS, & FOREIGN DIRECT INVESTMENT (FDI) TERHADAP CADANGAN DEVISA INDONESIA PERIODE TAHUN 1980-2017 - A.A. Bagus Putu Widanta, Sabili Mustaqim (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2021)
Foreign exchange reserves are defined as all foreign assets held by the monetary authority and can be used at any time to finance the balance of payments balance or in the context of monetary stability. The purpose of this study was to determine the effect of exchange rates, FDI and exports simultaneously on Indonesia's foreign exchange reserves. To analyze the effect of exchange rates, FDI and exports partially on Indonesia's foreign exchange reserves. The data used in this study are secondary using multiple linear regression analysis techniques and the classical assumption test. The results show that simultaneous exports, exchange rates, and FDI have a significant effect on Indonesia's foreign exchange reserves. The results of this study mean that the increase in exports, exchange rates and FDI can affect the increasing number of Indonesia's foreign exchange reserves. Partially, exports have a positive and significant effect on foreign exchange reserves. The exchange rate is partially positive and significant effect on foreign exchange reserves. FDI partially has insignificant effect on foreign exchange reserves.